Crystalline silicate absorption at 11.1 μm: ubiquitous and abundant in embedded YSOs and the interstellar medium. Issue 3 (12th February 2020) - Do-Duy, Tho; Wright, Christopher M; Fujiyoshi, Takuya; Glasse, Alistair; Siebenmorgen, Ralf; Smith, Robert; Stecklum, Bringfried; Sterzik, Michael
ABSTRACT: Utilizing several instruments on 4–8 m telescopes, we have observed a large sample of objects in the mid-infrared (8–13  μ m). These comprise a few evolved stars, multiple envelopes of embedded young stellar objects (YSOs) or compact H-II regions, and several sightlines through the interstellar medium (ISM). The latter is where dust resides – and is potentially modified – between its formation in evolved stellar outflows and deposition in molecular clouds. In most objects, we detect not only the well-known 9.7  μ m absorption feature of amorphous silicates but also a second absorption band around 11.1  μ m whose carrier is attributed to crystalline forsterite. We propose that crystalline silicates are essentially ubiquitous in the ISM and earliest phases of star formation, and are evolutionary precursors to T-Tauri and Herbig stars where such silicates have been commonly found. Modelling shows that in most YSOs, H-II regions and ISM cases, the forsterite mass fraction is between 1 and 2 per cent, suggesting that the younger phases inherit their abundance from the ISM. However, several sources show much stronger features (abundances ≥3 per cent). This suggests that significant processing, perhaps crystallization by thermal annealing, occurs early on in star formation. Most intriguing is the first detection of crystalline silicate in the diffuse ISM. We propose that our observed abundance is consistent with a mass fraction of crystalline silicates of 10–20 per cent injected into the ISM, along with commonly accepted lifetimes against their destruction, but only if cosmic ray-induced amorphization is insignificant over a few Giga years.